Prevalence of hypercholesterolemia in elderly Costa Ricans - Aguilar Fernández, Eduardo (2012)
This  paper  estimates  the  prevalence  of  hypercholesterolemia  (with  or  without  previousdiagnose) in elderly Costa Ricans. Too explore the factors associated to hypercholesterolemiacontrolled in elderly with previous diagnose. Data for this study come from a nationallysample of CRELES: “Costa Rica: Longevity and Healthy Agin Study”. Hypercholesterolemiaprevalence is 59,5% in elderly Costa Ricans. Prevalence for elderly with previous diagnose is68%  according  study´s  data  and  is  higher  in  females  than  males.  This  difference  wassignificant. The principal factors associated with hypercholesterolemia controlled are: malegender, have diabetes and hypertension diagnose, physical activity and take a drug for lipidscontrol. The drug interaction was not significant according the study´s data.